Comment on “Study on Mencius’ theory of human nature and moral concepts” - Zhao, Yan (2025)
Commented article: DENG, J. F. Study on Mencius’ theory of human nature and moral concepts. Trans/Form/Ação, Marília, SP, v. 47, n. 5, p. e02400198, 2024. Available at:  https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15149.